Dynamic Neural Mobilization Versus Proprioceptive Neuromuscular Facilitation on Grip Strength and UpperLimb Function in Sub-Acute Stroke Subjects. - Selvaraj, Angel Caralin; kunduru, Sudheera (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Neural mobilization and Proprioceptive Neuromuscular Facilitation (PNF) help in reducing spasticity, improve muscle flexibility and balance, enhancing mobility and elasticity of the nervous system in stroke subjects. Objectives: The objective of the study was to compare the effect of Dynamic Neural Mobilization and PNF on grip strength and upper limb function in sub-acute stroke subjects. Materials and methods: 30 post-stroke subjects were recruited and were randomly divided into two groups. 15 subjects in Group A received Dynamic Neural Mobilization while 15 subjects in Group B received PNF. The treatment sessions were scheduled for 30 minutes per day, 5 times a week, for 4 weeks. Subjects were assessed for upper limb function and grip strength prior to- and post-intervention using Fugl Meyer Assessment-Upper Extremity (FMA-UE) subscale and Hand Held Dynamometer. Results: Pre-test score of FMA-UE and grip strength were 33.60±7.13 and 2.92±1.07 in Group A and 32.60±9.85 and 1.70±0.68 in Group B respectively. The post-test scores of FMA-UE and grip strength were 41.00±7.07 and 5.12±203 in Group A and 34.13±10.40 and 3.32±0.82 in Group B. Within group comparison showed significant improvement in Group A and in grip strength of Group B subjects. FMA-UE in Group B did not show significant results compared to pre-test scores. Between groups comparison showed statistically significant improvement in Group A in both the outcomes. Conclusion: Based on the results, it can be concluded that Dynamic Neural Mobilization was more effective than PNF in improving grip strength and upper limb function in subacute stroke subjects.